2015
DOI: 10.3389/fmicb.2015.01171
|View full text |Cite
|
Sign up to set email alerts
|

Panamanian frog species host unique skin bacterial communities

Abstract: Vertebrates, including amphibians, host diverse symbiotic microbes that contribute to host disease resistance. Globally, and especially in montane tropical systems, many amphibian species are threatened by a chytrid fungus, Batrachochytrium dendrobatidis (Bd), that causes a lethal skin disease. Bd therefore may be a strong selective agent on the diversity and function of the microbial communities inhabiting amphibian skin. In Panamá, amphibian population declines and the spread of Bd have been tracked. In 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
112
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(138 citation statements)
references
References 65 publications
16
112
0
2
Order By: Relevance
“…, Belden et al . ). To assess temporal changes in bacterial community diversity, we swabbed each clutch two times: once 2.5 days after oviposition and again 5.5 days after oviposition, which is approximately 1.5 days prior to hatching competence for this population (J. Delia, unpubl.…”
Section: Methodsmentioning
confidence: 97%
“…, Belden et al . ). To assess temporal changes in bacterial community diversity, we swabbed each clutch two times: once 2.5 days after oviposition and again 5.5 days after oviposition, which is approximately 1.5 days prior to hatching competence for this population (J. Delia, unpubl.…”
Section: Methodsmentioning
confidence: 97%
“…In this study, we tracked the presence and abundance of the probiotic bacterium J. lividum through time using two different techniques: bacterial culturing using selective media for rifampin-resistant strains (33) and 16S amplicon sequencing, which is a culture-independent technique increasingly used to describe the bacterial community structure in amphibians (14,45,58,68,69). Despite the great advantages of using 16S amplicon sequencing for community profiling, one caveat is that this method does not distinguish between the natural J. lividum and the rifampin-resistant inoculated strain.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified 5,981 bacterial OTUs on L. clamitans skin, and these communities were dominated by two Pseudomonas OTUs. Several members of the genus Pseudomonas are known to produce antifungal and antibiotic compounds, and their dominance on the amphibian skin may indicate a defensive function (14,31,45,69,71). A recent study on Bufo boreas boreas tadpoles that compared bacterial taxa with a B. dendrobatidis-inhibitory bacterial OTU database found that tadpoles hosted significantly more inhibitory OTUs than other life stages or environmental samples (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper should be read in conjunction with two others that show how the Panamanian frogs which had experienced a lethal fungal infection, have now overcome the infection via commensal microbes. 64,65 What was not mentioned however, is that these vertebrates contain toxins that almost certainly are adsorbed from their diet of specific ants.…”
Section: Insect-microbe Symbiosesmentioning
confidence: 99%